2022
DOI: 10.3389/fmolb.2022.958586
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Structural Insights on the Poplar Tau Glutathione Transferase GSTU19 and 20 Paralogs Binding Flavonoids

Abstract: Glutathione transferases (GSTs) constitute a widespread superfamily of enzymes notably involved in xenobiotic detoxification and/or in specialized metabolism. Populus trichocarpa genome (V4.1 assembly, Phytozome 13) consists of 74 genes coding for full-length GSTs and ten likely pseudogenes. These GSTs are divided into 11 classes, in which the tau class (GSTU) is the most abundant with 54 isoforms. PtGSTU19 and 20, two paralogs sharing more than 91% sequence identity (95% of sequence similarity), would have di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…This showed that the site where the zwitterionic fragment of GSH was located was an electrophilic site. This property is verified in the crystallographic structures of glutathione-free GSTs because they often contain a negative ion in this site such as chloride, acetate or formate ions [ 56 ]. In addition, this electrophilic site was found to be catalytically important as it hosts the γ-Glu carboxylate group which is presumed to decrease the pKa of the GSH thiol group [ 57 ].…”
Section: Resultsmentioning
confidence: 98%
“…This showed that the site where the zwitterionic fragment of GSH was located was an electrophilic site. This property is verified in the crystallographic structures of glutathione-free GSTs because they often contain a negative ion in this site such as chloride, acetate or formate ions [ 56 ]. In addition, this electrophilic site was found to be catalytically important as it hosts the γ-Glu carboxylate group which is presumed to decrease the pKa of the GSH thiol group [ 57 ].…”
Section: Resultsmentioning
confidence: 98%